Estudo da prevalência de dentes supranumerários em pacientes indicados ao tratamento ortodôntico através de radiografias panorâmicas - Negrete, Daniel (2008)
There are several alterations in the dental arch, which can be in the number, shape or size of teeth. The supernumerary teeth represent an important etiologic factor of malocclusion, quietly frequent. This study’s goal was to evaluate the prevalence of supernumerary teeth in the patients who has been orthodontic treated in the graduation course of University of São Paulo City (UNICID). The evaluated material consisted in panoramic radiographs from these patients, from the files of the UNICID orthodontic department. The sample was studied regarding the prevalence distribution among gender, dental arches and oral regions. The results were submitted to descriptive statistical analysis. Pearson Chi-square and Binomial Probability tests were applied to compare the prevalence indexes. In 1117 samples of radiographs, 56% from female and 44% from male subjects, only 18 (1.61%) showed supernumerary teeth. Considering the gender, in 626 female radiographs, 1.9% presented supernumerary teeth and in 491 female radiographs, 1.2% showed supernumerary teeth. We not found statistically significant differences between males and females. The mean age of subjects was 13.7 years old. In total, we observed 24 supernumerary teeth, 16 was located on superior arch and 8 on inferior arch. In conclusion, our study indicate that the supernumerary teeth prevalence was 1.61% in total number of subjects, in males 1.2% and 1.9% in females, however, no statistical differences was observed between theses values. The prevalence of supernumerary teeth was statistically similar in superior and inferior arch, despite 66.7% was located in superior arch.